Post-viral idiopathic purpura fulminans is associated with inherited thrombophilia and anti-cardiolipin antibodies - Theron, A.; Ayadi, S.; Boissier, E.; Dautremay, O.; Schved, J.-F.; Sirvent, N.; Diaz, I.; Captier, G.; Biron-Andreani, C.; Jeziorski, E. (Frontiers in Pediatrics, 2023)
Introduction: Idiopathic purpura fulminans (IPF) is a rare and severe coagulation disorder, associated with transient anti-protein S (anti-PS) antibodies in the context of post-viral infection such as varicella. Anti-protein S antibodies are frequently found in the context of varicella, in contrast with the rarity of IPF. Other factors such as anti-phospholipid antibodies (APL) and inherited thrombophilia may be associated with severe vascular complication. Method: This is an ancillary study of a French multicenter retrospective series and systematic review of literature. We analyzed patients who were tested for inherited thrombophilia, namely antithrombin, protein C, protein S deficiency; prothrombin gene G20210A polymorphism (FII:G20210A),Factor V R506Q polymorphism (FV:R506Q); and/or for APL (lupus anticoagulant (LA), anti-cardiolipin antibodies (ACL), or anti-beta 2-GPI antibodies (Aβ2GP1). Results: Among the 25 patients tested for inherited thrombophilia, 7 (28%) had positive results. Three had FV R506Q, two FII:G20210A, one compound heterozygote FV:R506Q associated to FII:G20210A, and one protein C deficiency. APL testing was performed in 32 patients. It was positive in 19 patients (59%): 17 ACL (53%), 5 LA (16%), 4 Aβ2GP1 (13%). The risk of severe complications was not associated with presence of inherited thrombophilia or APL presence, with RR: 0.8 [95% CI: 0.37–1.71], p=1 and RR: 0.7 [95% CI: 0.33–1.51], p=0.39, respectively. We found a high prevalence of inherited thrombophilia or APL in a population of patients with IPF. However, we do not find an association with the occurrence of severe vascular complications or venous thromboembolism.